End-of-Life Preferences in Afro-Caribbean Older Adults: A Systematic Literature Review. (November 2014) - Moss, Karen O.; Williams, Ishan C.
Research suggests that older Blacks tend to prefer more aggressive treatment as they transition toward the end of life. African and Afro-Caribbean immigrants and their offspring are the fastest growing segments of the Black population in the United States. With the increasing population of Black older adults, the cost of end-of-life care is rising. This article presents a review of the literature on the end-of-life preferences of Afro-Caribbean older adults. Findings suggest that Afro-Caribbean older adults make end-of-life decisions with a significant emphasis on family structure, religion/spirituality, cultural identity, migration, and communication. Concerns regarding the meaning of end-of-life preparation and hospice are often viewed in ways that differ from that of healthcare providers. Future research is needed to investigate this process in the Afro-Caribbean older adult subset.